THE FRAGILITY OF THE GLOBAL SUPPLY CHAIN: A STUDY ON BEVERAGES ALCOHOLIC BUSINESS IN INDIA - Shetty, Santosh (Digital Repository of Theses - SSBM Geneva, 2023)
This study focuses on the fragility of the Global Supply Chain (GSC), specifically within the alcoholic beverages (Alco Bev) industry in India. The study highlights several factors that contribute to this vulnerability, including limited supplier diversification, regulatory hurdles, transportation and logistics challenges, geopolitical factors, natural disasters and climate change, cybersecurity threats, and insufficient risk management strategies, among others. An extensive literature review underscores the importance of strengthening Global GSCs to enhance their resilience in the face of disruptions. The review explores the challenges faced by the Alco Bev industry during the Covid-19 pandemic and examines the strategies implemented to mitigate its impact. The study reveals that pandemic-related disruptions significantly affected the industry, leading to increased costs and delivery delays. Therefore, it emphasizes the necessity of a flexible and resilient GSC capable of adapting to unforeseen events such as the pandemic. The study employed as well as included document analysis and survey questionnaires, to gain insights into key stakeholders, service providers, and institutions involved in the Alco Bev industry. Furthermore, the target audience for the study encompassed various entities within the industry, such as manufacturers, wholesalers, retailers, various logistics service providers, customs house agents, duty-free operators, and Customs bonded warehouse operators. The survey questions were designed and mapped to address eight research questions concerning the strategies employed by Alco Bev organisations in navigating the challenges of the GSC during the pandemic. The study's results, based on responses from 66 survey participants, highlighted the significance of robust and resilient GSCs in improving overall performance. It was suggested that international collaboration could play a crucial role in mitigating GSC interruptions by facilitating the maintenance of normal operations during unforeseen circumstances. Furthermore, the study recommended the utilisation of artificial intelligence as a tool for predicting and preventing SC disruptions and emphasised the importance of collaboration between SC organisations and mass media organisations to address issues such as fake news, consumer panic, and cost increases. Finally, the study proposed areas for future research, including evaluating the regulatory framework, analysing the role of technology, examining the effects of climate change, assessing sustainability, and studying the impact of geopolitical risks. Overall, the study emphasised the fragility of the GSC and the need for proactive measures to enhance its resilience in the Alco Bev industry in India.